1988
DOI: 10.1071/mf9880555
|View full text |Cite
|
Sign up to set email alerts
|

Growth in the Australian freshwater crayfish, Cherax destructor Clark, under laboratory conditions

Abstract: Small (0.08 to 6.1 g) crayfish were grown at 26�C under three treatments: held individually and fed 3% or 10% of body weight per day, or held communally and fed the higher ration. Moult increments, expressed as length or weight increment (%), were smaller and intermoult periods were longer in the crayfish held communally or, particularly, in crayfish fed low rations; this resulted in lower growth in these treatments. Crayfish from three geographically discrete populations held individually and fed the higher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Percentage consumption of food decreased as animals grew, and is consistent with the reduced metabolic requirement with size (Musgrove, 1993). Growth in this trial was slower than that reported for similar sized yabbies fed natural diets in intensive culture conditions (Geddes et al, 1988;Jones et al, 1995), or in pond production environments (Mills and McCloud, 1983;. This highlights the necessity for additional detailed studies, to identify the growth enhancing components present in the natural diet of these crayfish.…”
Section: Discussionmentioning
confidence: 42%
“…Percentage consumption of food decreased as animals grew, and is consistent with the reduced metabolic requirement with size (Musgrove, 1993). Growth in this trial was slower than that reported for similar sized yabbies fed natural diets in intensive culture conditions (Geddes et al, 1988;Jones et al, 1995), or in pond production environments (Mills and McCloud, 1983;. This highlights the necessity for additional detailed studies, to identify the growth enhancing components present in the natural diet of these crayfish.…”
Section: Discussionmentioning
confidence: 42%
“…The demonstration that intraspecific variation in morphology and growth exists in C. destructor is consistent with the results from other smaller‐scale trials that have examined this issue in this species. Geddes, Mills & Walker (1988) found variation in the relationships describing growth increment and intermoult period among three yabby populations from South Australia and Queensland. Faster growth was attributable to larger growth increments in proportion to body size, coupled with decreased intermoult periods.…”
Section: Discussionmentioning
confidence: 87%
“…The demonstration that intraspecific variation in morphology and growth exists in C. destructor is consistent with the results from other smaller-scale trials that have examined this issue in this species. Geddes, Mills & Walker (1988) found variation in the relationships describing growth increment and Sexes that are significantly different for mean weight are indicated by different superscripts and were determined using the SNK test with the experiment-wise error rate a 0.05; n number of juveniles per sex. Table 5 Mean proportion of abdomen length against total body length (AL/(OCL TL)) and SEM for sex and each of the five yabby populations at the four measurement periods intermoult period among three yabby populations from South Australia and Queensland.…”
Section: Discussionmentioning
confidence: 99%
“…Higher frequency of molts indicates a faster rate of growth, which on one hand is beneficial; however, it also leads to a critical event in these animals' lives by making them vulnerable to attacks by conspecifics that are often their predators. Studies carried out in other Australian parastacids showed that individual rearing systems had a higher survival rate than communal rearing (Geddes et al 1988;Du Boulay et al 1993;Morrissy et al 1995). On the other hand, the higher risk of mortality due to cannibalism at the early stages of life than in the later stages may partially explain the higher survival rate of advanced juveniles compared to that of early juveniles.…”
Section: Discussionmentioning
confidence: 95%